2022
DOI: 10.1109/access.2022.3195028
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Fake and Real Smiles Using Electroencephalogram Signals With Convolutional Neural Networks

Abstract: Genuineness of smiles is of particular interest in the field of human emotions and social interactions. In this work, we develop an experimental protocol to elicit genuine and fake smile expressions on 28 healthy subjects. Then, we assess the type of smile expressions using electroencephalogram (EEG) signals with convolutional neural networks (CNNs). Five different architectures (CNN1, CNN2, CNN3, CNN4, and CNN5) were examined to differentiate between fake and real smiles. We transform the temporal EEG signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Yang et al [44] validated their CNN model by comparison with k-NN, SVM, LDA, and other CNN models. Moussa et al [51] demonstrated the effectiveness of CNN models through comparison with LSTM, ANN and SVM. Similarly, Farokhah et al [52] validated the efficiency of the simplified CNN models.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yang et al [44] validated their CNN model by comparison with k-NN, SVM, LDA, and other CNN models. Moussa et al [51] demonstrated the effectiveness of CNN models through comparison with LSTM, ANN and SVM. Similarly, Farokhah et al [52] validated the efficiency of the simplified CNN models.…”
Section: Methodsmentioning
confidence: 99%
“…EEG signals have been analyzed to create BCI systems using analysis techniques such as EEG feature extraction from an event-related potential (ERP) response [11], the power spectrum and spectral centroid [13][17]- [19], Bayesian-based EEG feature extraction techniques [20], principal component analysis [21]- [24], independent component analysis (ICA) [15] [23][25]- [27], EEG pattern classifiers, artificial neural networks (ANN) [14][23] [28], k-nearest neighbor algorithm [29] [30], linear discriminant analysis (LDA) [15][31]- [33], SVM [12][13] [21][34]- [37], self-organizing maps [38], and fuzzy entropy [39]. Furthermore, over the past few years, DNN, its improved models [7][8][40]- [44], and convolutional neural networks (CNN) [9][10][45]- [51] have been employed for EEG feature extraction and pattern classification. In particular, EEGNET was proposed as the dedicated EEG analysis model based on artificial intelligence techniques [46][52]- [55].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations